Research and Practice on Teaching Strategies for AI-enabled Writing and Communication Courses - Zhou, Zhiling (Journal of Research in Vocational Education, 2025)
This paper focuses on the teaching reform of writing and communication courses under the background of AI empowerment, and deeply analyzes the teaching strategy of “one core, three synergies and five linkages”. By building a collaborative integration mechanism of “context creation-task drive-curriculum ideological and political education”, the traditional teaching model is broken; relying on the five-link linkage closed-loop teaching process of “examination-evaluation-learning-practice-thinking”, the teaching quality is spirally improved; leveraging AI technology to reconstruct courses and create an industry-university-research-education community, it provides innovative ideas and replicable practical solutions for the teaching reform of liberal arts courses, effectively improving college students’ writing and communication skills and helping them develop in an all-round way.